Merancang Model Pemaknaan Bersama Kitab Suci Kontekstual untuk Meningkatkan Resiliensi ODHA di Maumere - Servinus Haryanto Nahak; Maximinus Hali Abit; Louis Diego Liko (Jurnal Penelitian Pendidikan Agama Katolik, 2026)
People living with HIV/AIDS (PLWHA) are a vulnerable group who often experience stigma and discrimination in society. In facing this difficult situation, PLWHA need to have adequate self-resilience to survive and be productive. PLWHA have undertaken various activities to improve their self-resilience. One of the routine monthly activities is Bible sharing. However, the model used is still conventional and not contextualized to the spiritual needs and experiences of PLWHA. This qualitative research using the Interpretative Phenomenological Analysis (IPA) approach aims to construct a model of Bible sharing as a strategy to improve the self-resilience of PLWHA. Ten informants participated in this study. Data were collected through in-depth interviews and participant observation. An in-depth analysis of the self-resilience of PLWHA in the Flores Plus Support Group (PSC) in Maumere revealed that they experience negative self-image, psychological distress, future concerns, and social withdrawal. Regarding Bible sharing activities to date, PLWHA provided critical comments, particularly regarding the lack of talented facilitators and the involvement of monks and nuns, as well as the lack of supporting resources such as monotonous guiding questions and a lack of technological tools. These results indicate the urgent need for a Bible sharing model to enhance the self-resilience of PLWHA.